Population exchange in Greek Macedonia : the rural settlement of refugees 1922-1930 - Kontogiōrgē, Elisavet (Oxford historical monographs., 2006)
Following the defeat of the Greek Army in 1922 by nationalist Turkish forces, the Convention of Lausanne in 1923 specified the first compulsory exchange of populations ratified by an international organization. The arrival in Greece of over 1.2 million refugees and their settlement proved to be a watershed with far-reaching consequences for the country. Elisabeth Kontogiorgi examines the agricultural settlement of a great number of refugees in Greek Macedonia against the background. of forced migration and refugee studies more generally. - ;Following the defeat of the Greek Army in 1922 by nat.